THE EFFECT OF AUTHENTIC MATERIALS ON THE NINTH GRADE STUDENT’S READING COMPREHENSION AT SMP NEGERI 4 KOTA TANGERANG - Fuji Devi Riani; Yudhie Indra Gunawan; Imtihan - Hanim (Universitas Muhammadiyah Tangerang, 2021)
This research was conducted at SMPN 4 KOTA TANGERANG which took place from July to August. The sample consisted 76 students from ninth grade which devide into two classes, experimental class (IX.3) and controlled class (IX.4).Based on the observation, some of students feel that learning of English, especially in reading is difficult subject compared to other lessons. So, the researcherss conduct research with used the Authentic Material with the aim in this research is to find and know whether that authentic material’s effect or not on students’ reading comprehension. This research used a quantitative method with a quasiexperimental design. In collecting the data, the researcherss gave pre-test and post-test on both classes with mulitiple choice questions that had been tested for validity and reliability before and in analyzing the data the researchers used t-test. Hyphothesis test result as the degree of significant 5% indicates that pre-test done before treatment is Tcount (1,22982) < Ttable 1,992543, so H0 is accepted and H1 is rejected or there is no significant effect from experimental class and the controlled class before giving a treatment. It was found that posttest done after treatment isTcount (2,24132) > Ttable 1,992543, so H0 is rejected and H1 is accepted. The result of this research shows that there is significant difference on students’ reading comprehension by using authentic materials.Therefore, it can be interpreted that teaching reading by using authentic materials can increase the students’ comprehension.